PENGARUH PREDIKSI KEBANGKRUTAN TERHADAP HARGA SAHAM PERUSAHAAN - ARDIANSYAH RAMADHAN, FERRY; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2018)
This study aims to determine the effect of bankruptcy predictions on the companys stock price. This study uses 20 state-owned companies that are listed on the IDX in the period 2012-2016 as a population. The criteria of the company that were sampled for this study were companies that indicated financial distress and healthy companies in the Altman z-score calculation. The multiple linear regression analysis model is the model set in this study. The results showed that regression shows the prediction of bankruptcy by the Altman z-score method which affects stock prices. Firm size control variable shows the results there is an influence on stock prices. The growth control variable shows that there is no effect on stock prices.Key Words : bankruptcy prediction, Altman z- score, financial distress, multiple linear regression